Addressing Practices in Mata Najwa Show: A Sociolinguistic Approach to Media Discourse - Maemuna Muhayyang; Muh.Fakhrul Armas; Syamsiarna Nappu (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
Addressing refers to the words or phrases used by speakers to address interlocutors during a conversation. It plays a significant role in communication, reflecting various social factors such as hierarchy, familiarity, and politeness. This study examines the types of addressing used by Najwa Shihab in the Mata Najwa Show, focusing on how different address terms are employed in formal settings. A descriptive qualitative approach was used, analyzing data from three episodes of the show, sourced from Najwa Shihab’s YouTube video titled “Ironi Korupsi Kala Pandemi.” The findings revealed four types of addressing: first names, kinship terms, titles, and special nicknames. Among these, kinship terms were most frequently used. The study also identifies that the choice of addressing terms was influenced by factors such as social status, age, politeness, and the degree of closeness between the speaker and the interlocutor. The results suggest that addressing practices in formal settings are complex and context dependent. Future research could explore how cultural contexts and power dynamics influence addressing practices in media discourse.